Social capital deviation in capital assistance system: Socio-economic studies of coastal communities - Mochamad Ridwan; Akhsanul In'am (Economies, 2021)
Revealing the practice of the capital assistance system in coastal communities that are indicated to have deviated from the principles of social capital, and building an integrated model as a solution for improving fishermen's low performance are the main objectives of this study. For this purpose, fishermen communities were chosen as the research sample. The research locations were focused on two provinces in Indonesia (Bengkulu and East Java provinces). Data were collected through observation, interview, and documentation methods. Discriminant and SEM/SmartPLS analysis methods were used to analyze quantitative data, while the descriptive analysis method was used to analyze qualitative data. The results show that the implementation of the capital assistance system by well-off fishermen (as capital providers) was proven to deviate from the principles of social capital because it was detrimental to small-scale/traditional fishermen. Six factors cause deviations in the capital assistance system: (a) the lack of "altruism cooperation" between well-off fisherman and small-scale/traditional fishermen; (b) mutual trust is not developed; (c) the powerlessness of the fishing community, which desperately needs funds for working capital; (d) government control is not effective; (e) the role of cooperative institutions (fisheries) as providers of funds/loan capital is still weak; and (f) an empowerment integrated model is considered capable of providing a comprehensive solution.
Keywords: 330; capital assistance system; fishermen; marine natural resources; performance; social capital